SISTEM INFORMASI MANAJEMEN JEMBATAN BERBASIS WEB DENGAN METODE BRIDGE CONDITION RATING (Studi Kasus Pengelolaan Jembatan di Kabupaten Garut) - Subagio, Gatot; Triwiyono, Andreas; Satyarno, Iman (Civil Engineering Forum Teknik Sipil, 2008)
A state progression level can be identified from the infrastructure demand. However, infrastructure projects requires high investment cost, therefore it is recessary to optimally maintain the existing infrastructure facility. Bridge management is required to maintain the bridge function and role, as well as to keep the bridge service period in line with the service period plan by using various efforts to maintain the safety, comfort, and economy in serving the traffic. The bridge management needs a lot of recent information of the bridge inventory and condition. It is required to build accurate and up-to-date information for bridge management completed with DSS (Decision Support System) to make the inventorying result to be easily understood and to determine bridge management priority. Research area in producing this system was located at Garut Regency, West Java by taking 7 bridges as samples, under Bina Marga Public Work management. WEB-based Bridge Management Information System (SIMJWEB) was software built with PHP (PHP Hypertext Preprocessor) and MySQL Database Management System. The bridge condition is visually assessed using the Bridge Condition Rating method of NYSDOT (New York State Department of Transportations). Bridge component is assessed based on Component Rating of 7 as good and 1 as worst. The total Component Rating is multiplied with Weight Factor from each component, and then divided by total Weight Factor resulting from Bridge Condition Rating that reflects the bridge condition. Treatment priority determination is based on Bridge Condition Rating Value. Information on treatment time delay is obtained from estimated bridge service period using IBMS (Interurban Bridge Management System) assumption. SIMJWEB is able to provide prompt information on the inventory, condition, proposal and management priority data, as well as the estimation of bridge service period. Such information helps the bridge manager in making decision. Through internet media, bridge user can actively participate to bridge management in a region by giving idea or following public hearing made by bridge manager. This research results show that Cipancar 1 Bridge has the highest treatment priority at condition rating of 4.874 and requires rehabilitation as the proposed treatment. The lowest priority is Cimanuk Andir bridge at condition rating of 6.587 and requires regular and periodic maintenance as the proposed treatment. By estimating that Cipancar 1 bridge plan period is 50, the Equivalent period is 28.3 years and in 22 years later, the bridge function would not be functioned anymore.